IMPROVEMENTS OF THE FOOD SAFETY MANAGEMENT SYSTEM BROUGHT BY THE ISO 22000:2018 WITH APPLICABILITY TO THE CANTEEN OF THE „VASILE ALECSANDRI” UNIVERSITY OF BACAU - MARIA-CRINA RADU; RODICA BUCUROIU; LUMINITA GROSU (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
This paper aims to summarize the conceptual changes brought by the ISO 22000:2018 to the food safety management systems and to present a practical approach to their implementation. A case study is carried out for the canteen of the „Vasile Alecsandri” University of Bacau (UBc), a Romanian university that has implemented a food safety management system (FSMS) since 2012, which must be updated to the new requirements of the standard by the end of the transition period. Due to the large amount of work involved in such a task, the analysis included in this paper addresses only the first new clauses of the standard – understanding the organization and its context and understanding the needs and expectations of interested parties, respectively, in the light of a riskbased thinking approach.